Impact of a Traditional Dietary Supplement with Coconut Milk and Soya Milk on the Lipid Profile in Normal Free Living Subjects - R. A. I. Ekanayaka; N. K. Ekanayaka; B. Perera; P. G. S. M. De Silva (Journal of Nutrition and Metabolism)
Background. The effects of coconut fat and soya fat on serum lipids are controversial. This study was designed to investigate the lipid effects of coconut milk and soya milk supplementation on the lipid profile of free living healthy subjects. Methods. Sixty (60) healthy volunteers aged 18–57 years were given coconut milk porridge (CMP) for 5 days of the week for 8 weeks, followed by a 2-week washout period, subsequent to which they received isoenergetic soya milk porridge (SMP) for 8 weeks. Results. The LDL (low density lipoprotein) levels decreased with CMP and reached statistical significance in the total study population and in the >130 baseline LDL group. The HDL (high density lipoprotein) levels rose significantly with CMP supplementation (P=0.000). Conclusions. We conclude that coconut fat in the form of CM does not cause a detrimental effect on the lipid profile in the general population and in fact is beneficial due to the decrease in LDL and rise in HDL. SMP will be of benefit only in those whose baseline LDL levels are elevated.